Tungsten Oxide Nanoplates: Facile Synthesis, Controllable Oxygen Deficiency and Photocatalytic Activity - Nguyen, Van Thai; Nguyen, Hong Son; Pham, Van Thang; Nguyen, T. Tuyet Mai; Luu, T. Lan Anh; Nguyen, Huu Lam; Nguyen, Duc Chien; Nguyen, Cong Tu (Communications in Physics, 2020)
Monoclinic tungsten oxide (WO3) nanoplates were synthesized via a two-step simple process: acid precipitation at room temperature to prepare WO3.H2O nanoplates and annealing at high temperature (400 and 500 oC) in ambient air to obtain WO3 nanoplates. The effect of annealing temperature on physical properties (morphology, oxygen deficiency, crystallinity, optical properties, and photocatalytic activity) of WO3 nanoplates was studied. At both two studied annealing temperatures, all samples have the stable monoclinic structure and visible light-range optical bandgap, but the morphology and photocatalytic activity of the samples vary significantly with annealing temperature. At higher annealing temperature (500 oC), the sample has both nanoplate and nanograin morphologies with round edges, higher crystallinity, larger optical bandgap (2.71 eV), and lower photocatalytic activity. The sample annealed at 400 oC has nanoplate morphology with sharp edges, lower optical bandgap (2.63 eV), and higher photocatalytic which shows a high potential for photocatalytic application under visible light irradiation. The effect of the annealing temperature on the properties of  WO3 nanoplates is assigned to the dehydration, the coalescence, and/or the melting processes at high temperatures. Dehydration causes the formation of oxygen vacancy – oxygen deficiency. The coalescence and/or the melting result in the changing of morphology and the decrease of the oxygen vacancies. These results imply a simple, cost-effective method to prepare highly oxygen-deficient WO3 nanoplates.